Electron traps in solid Xe - Khyzhniy, Ivan V.; Uyutnov, Sergey A.; Savchenko, Elena V.; Gumenchuk, Galina B.; Ponomaryov, Alexey N.; Bondybey, Vladimir E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Correlated real-time measurements of thermally stimulated luminescence and exoelectron emission from solid Xe pre-irradiated with an electron beam were performed. The study enabled us to distinguish between surface and bulk traps in solid Xe and to identify a peak related to electronically induced defects. The activation energy corresponding to annihilation of these defects was estimated by the following methods: the method of different heating rates, the initial-rise method, and the curve cleaning technique with fitting of the thermally stimulated luminescence glow curve.